Moderation of Gender and School Location on the Prediction of Test Anxiety on Physics Students’ Academic Achievement in Waves Motion - Ocheni, Christopher Adah; Okeke, Agnes Obianuju; Agah, John Joseph; Oguguo, Basil C. E.; Ene, Catherine Uzo; Ezugwu, Ifesinachi Jude; Asongo, Stanley T (Physics Education Research Journal, 2024)
The continuous decline in students’ achievement in physics, especially in wave motion, has become a significant concern among education stakeholders. This study, which examines the moderation of gender and school location in predicting test anxiety on students` achievement in wave motion in physics, offers actionable recommendations for improvement. A correlational research design was adopted. Three research questions and three hypotheses informed the study. A sample of 337 students drawn through a multistage sampling procedure was used for the study. Waves Test Anxiety Inventory (WTAI) and Waves Achievement Test (WAT) instruments were used for data collection. Reliability indices of 0.73 and 0.76 using Cronbach alpha and KR-20 were estimated for WTAI and WAT, respectively. The research questions were answered using regression analysis, while ANOVA and t-test results obtained using Hayes` Process Macro were used to test the hypotheses at a 0.05 significance level. Results showed that test anxiety significantly predicts students` achievement in wave motion. The results showed that the moderation of gender in test anxiety prediction was insignificant. However, the location significantly influenced the prediction of test anxiety on students` achievement in wave motion. It was recommended, among others, that physics teachers ensure that lesson contents are duly covered and that a conducive learning environment, clear instructions, and adequate preparations are made available to students before testing them, thereby potentially improving students' academic performance.